2007
DOI: 10.1094/ats-2007-0831-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Selection and Application Timing in the Fall Affects Control of Ground Ivy

Abstract: Specific timing of fall applications of broadleaf weed herbicides is not refined to maximize control of ground ivy. The objective of our three‐year study was to determine how application timing in fall affects control of ground ivy with five different herbicide treatments. Herbicides were applied on 1 and 15 September, 1 and 15 October, and 1 and 15 November of 2003, 2004, and 2005. When rated in December following application, applications of all herbicides were most effective if applied prior to 1 November. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…Triclopyr reduced ground ivy cover compared with the untreated check in 2010–2011 but reduced ground ivy cover as well as aminocyclopyrachlor in 2011–2012. Similar to our research, others have observed that triclopyr and 2,4‐D ester provided the greatest control of ground ivy when applied in October (Kohler et al, 2004b; Reicher and Weisenberger, 2007). Reicher and Weisenberger (2007) observed poor ground ivy control from October and November applications of 2,4‐D + MCPP + dicamba.…”
Section: Influence Of Herbicides and Mowing On Ground Ivy Coversupporting
confidence: 91%
See 4 more Smart Citations
“…Triclopyr reduced ground ivy cover compared with the untreated check in 2010–2011 but reduced ground ivy cover as well as aminocyclopyrachlor in 2011–2012. Similar to our research, others have observed that triclopyr and 2,4‐D ester provided the greatest control of ground ivy when applied in October (Kohler et al, 2004b; Reicher and Weisenberger, 2007). Reicher and Weisenberger (2007) observed poor ground ivy control from October and November applications of 2,4‐D + MCPP + dicamba.…”
Section: Influence Of Herbicides and Mowing On Ground Ivy Coversupporting
confidence: 91%
“…Similar to our research, others have observed that triclopyr and 2,4‐D ester provided the greatest control of ground ivy when applied in October (Kohler et al, 2004b; Reicher and Weisenberger, 2007). Reicher and Weisenberger (2007) observed poor ground ivy control from October and November applications of 2,4‐D + MCPP + dicamba. In contrast, Vrabel (1987) observed excellent control of ground ivy with 2,4‐D + MCPP + dicamba within weeks of the initial application in the spring.…”
Section: Influence Of Herbicides and Mowing On Ground Ivy Coversupporting
confidence: 91%
See 3 more Smart Citations